Optimized High-Gain DC-DC Converter for PV Applications - Harmini, Harmini; Titik Nurhayati; Supari; Priyo Adi Sesotyo; Satria Pinandita; Ery Sadewa (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
Photovoltaic (PV) systems frequently encounter low and fluctuating output voltages, which can significantly impede efficient energy utilization and necessitate more advanced power conversion solutions. Addressing this challenge, the study aims to develop a high-gain DC-DC converter topology that offers stable voltage regulation, making it suitable for PV applications. The proposed solution targets the essential need for substantial voltage boosting while maintaining reliable performance even under varying solar irradiance conditions. The core of the design is based on a Quadratic Boost Converter (QBC) integrated with Voltage Multiplier Cells (VMC), collectively referred to as QBC-VMC. This innovative configuration enhances the voltage gain capability compared to traditional converters. To ensure precise control of the output voltage, a Proportional-Integral (PI) controller is implemented. The system undergoes thorough analysis, including detailed modeling, simulation, and the design of its control structure, to optimize performance. The results demonstrate that the proposed converter can achieve a voltage gain of up to 12 times the input voltage. The PI controller effectively maintains a stable output voltage at approximately 600 V with a tolerable variation of ±0.7%. Additionally, the system exhibits an energy conversion efficiency approaching 81%, even under fluctuating irradiance conditions. This indicates a strong dynamic response and steady-state performance, essential for reliable PV operation. By integrating QBC-VMC with PI control, the proposed approach significantly enhances voltage stability and energy conversion efficiency. Overall, this system provides a promising solution for high-performance PV power systems, capable of delivering reliable power output under varying environmental conditions.